ANALISIS IMPLEMENTASI PENGELOLAAN SAMPAH MELALUI “SAHABAT SAMPAH” SEBAGAI INOVASI PENANGANAN SAMPAH DI KECAMATAN SAMBOJA - Syaiful Fadli (Jurnal Administrative Reform, 2021)
Analysis of the implementation of waste management through “Sahabat Sampah” as an waste management innovation in Samboja district. Syaiful Fadly, Graduate Program at Mulawarman University. This study aims to empirical analyze the implementation of waste management “Sahabat Sampah” as an waste management innovation in Samboja district. This study use a qualitative approach with the intention of obtaining a description of the implementation of waste management through in Samboha district. The data obtained were carried out by observation, documentation and interview techniques, which were then analyzed using descriptive analysis models with coding techniques. The result showed that the implementation of waste management policies in Samboja district through the role of Sahabat Sampah has been effective. Based on the 4 (four) indicator approach developed by Edward III (communication, resources, bureaucratic structure and disposition), it can be seen that the overall implementation of waste management policies has well done. Although in some aspect it still needs to be developed so that implementation can run more optimally. Among other things, the aspect of funding sources is still limited, so that becomes an obstacle to expanding the waste handling area. Then education and outreach to the community as a whole, so that awareness in handling and management of waste can be massively carried out, and involve all levels of society. Keywords: Garbage, Waste Management Implementation, Garbage Friends